THE EFFECT OF DEEP BREATHING RELAXATION TECHNIQUES ON BLOOD PRESSURE IN THE ELDERLY IN BATE LINTENG AND LAMBUNOT VILLAGES, ACEH BESAR - Rauzatul Jannah; Putra, Yadi; Andriani, Irma (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Hypertension is a chronic condition characterized by increased blood pressure on the artery walls, which can lead to serious complications such as stroke, kidney failure, and heart disease. This study aimed to determine the effect of deep breathing relaxation techniques on lowering blood pressure in elderly people in Bate Linteng and Lambunot Villages, Aceh Besar. This quantitative study used a pre-experimental design using a one-group pretest-posttest. The study was conducted from August 26 to August 31, 2024, with a population and sample of 16 elderly respondents with a history of hypertension. Data collection was conducted through observation using an observation sheet and the provision of deep breathing relaxation techniques. The results showed that the average blood pressure before the intervention was 148/90 mmHg with a standard deviation of 9.674, while after the intervention, it decreased to 143/87 mmHg with a standard deviation of 9.050. The statistical test results using the Paired Sample t-Test showed a significance value of 0.000 (p < 0.05), indicating a significant effect between deep breathing relaxation techniques and blood pressure reduction. The results of this study are expected to provide information for hypertension sufferers and their families that deep breathing relaxation techniques are a form of non-pharmacological therapy that can be performed independently to control blood pressure.